PENGEMBANGAN STRATEGI DAKWAH PADA MASYARAKAT MARGINAL - Masruq Masruq; Milawaty Waris (RETORIKA : Jurnal Kajian Komunikasi dan Penyiaran Islam, 2022)
The characteristics of different communities make the da'i strategy used by different of us. Carried out that the values ​​in Islamic teachings can be conveyed effectively and efficiently to mad'u. Especially da'wah among marginalized communities, of course starting from strategies, methods, materials, media and the characteristics of a da'i will also be different. This study discusses the da'wah strategy in marginalized communities. Where in general, marginalized communities have special characteristics that require da'wah that brings change towards progress. The results of this study explain that the development of da'wah strategies in marginalized communities can be carried out by strategic steps through practical steps and can also be done through coaching in the form of guidance, direction and assistance in studying Islamic teachings, providing an explanation of the correct understanding of Islam. based on the Qur'an and al-Hadith, collaborate with religious organizations (Islamic organizations) and scholars/kyai in the context of developing Islamic da'wah through da'wah strategies with the wisdom method, the bil-lisan method, the wal mujlah method, billati hiya ahsan and the bil-hal method and also through an Islamic study approach and using a social approach. This social approach is also the actualization of da'wah.